2001
DOI: 10.1300/j013v32n04_01
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Analysis of the Relationship Between Walking and Mood in Sedentary Ethnic Minority Women

Abstract: Walking for exercise is becoming widely recognized for bestowing health benefits. This study examined the association of walking for exercise and mood in sedentary, ethnic minority women over a five-month period. Ethnic minority women (N = 102) participated in a randomized, controlled trial of a 7-week behaviorally based telephone and mail intervention that promoted the adoption of walking for exercise compared to a non-behavioral minimal intervention. At 2-month post-test and 5-month follow-up, participants r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Several large studies have shown an inverse correlation between depression and physical activity in obese and overweight women (Beydoun & Wang, 2010; Simon et al, 2008). There is also some evidence that increasing physical activity is associated with decreased depressive symptoms in minority women (e.g., Ayala, 2011; Craft, Freund, Culpepper, & Perna, 2007; Lee et al, 2001; Perrino et al, 2011). However, few of these studies included large numbers of minority participants and therefore it is possible that for overweight or obese minority women, physical activity does not predict depression risk.…”
Section: Discussionmentioning
confidence: 99%
“…Several large studies have shown an inverse correlation between depression and physical activity in obese and overweight women (Beydoun & Wang, 2010; Simon et al, 2008). There is also some evidence that increasing physical activity is associated with decreased depressive symptoms in minority women (e.g., Ayala, 2011; Craft, Freund, Culpepper, & Perna, 2007; Lee et al, 2001; Perrino et al, 2011). However, few of these studies included large numbers of minority participants and therefore it is possible that for overweight or obese minority women, physical activity does not predict depression risk.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its relation to obesity, being physically active is itself related to decreased mortality and to decreased risk of many diseases including diabetes, some cancers, and cardiovascular disease (81,123,128). Being physically active is also related to psychological health, including positive mood and decreased depressive and anxiety symptoms (79,123). Yet, according to the Surgeon General as well as more recent epidemiological sources, more than 60% of Americans are not active enough to obtain important health benefits, and more than 25% are completely sedentary (123).…”
Section: Defining Physical Activitymentioning
confidence: 99%
“…Recent research offers some suggestions. A handful of empirical studies indicate that walking enhances cognition in terms of memory (Labonté-LeMoyne et al 2015;Schaefer et al 2010), divergent thinking (Oppezzo and Schwarz 2014), and cognitive control (Hillman et al 2009), prevents cognitive decline in the elderly (Erickson et al 2011;Weuve et al 2004), when in nature, reduces stress (Aspinall et al 2013;Jin 1992;Morita et al 2007), improves mood (Lee et al 2001;Sakuragi and Sugiyama 2006) and enhances creativity (Atchley et al 2012).…”
Section: Introductionmentioning
confidence: 99%